Multidisciplinary Audit of Hypertensive Disorders in Pregnancy with Autoimmune Comorbidities and Manifestations: Maternal, Fetal, Musculoskeletal, and Physiological Outcomes from a Cohort Study - Fauzia Dilshad, Priya Malhotra, Attiq ur Rehman, Nargis Haider, Aks-e Taqveen, Muhammad Azhar Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Severe hypertensive disorders in pregnancy (HDP) coexisting with autoimmune disease present acomplex clinical phenotype with multisystem consequences that span maternal, fetal,musculoskeletal and physiological domains.